(3GdJShjb GdGSJQGJjLj ddNOeGJ (B/s - (3eUWai, eMeO eMehOs ((3YeGf(B: s (3OGQ GdefGgL ddfTQ hGdJhRjY(B, s, 2008)
(3GdJNWjW GdJShjbj GdESJQGJjLj WHjYJg hCHYGOg, GSJQGJjLjGJ JUfja GdNOeGJ, GdESJQGJjLjGJ GdJShjbjI GdJfGaSjI aj GdNOeGJ, GSJQGJjLjGJ EOGQI GdYQV hGdWdH hGdEfJGLjI, ESJQGJjLjGJ JSYjQ GdNOeGJ, GSJQGJjLjGJ JQhjL GdNOeI, GSJQGJjLjGJ JbOje GdNOeGJ, ESJQGJjLjGJ LhOI GdNOeI, MGdGJ OQGSjI JWHjbjIs
(3HjHdjhZQGajG(B: (3U U(B.327-332s
Keywords: (3GdESJQGJjLjI GdJfGaSjIs; (3GdJShjbs; (3GdNOeGJs